2022
DOI: 10.3390/ijerph19052929
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Satisfaction with Life among Nursing Students in Poland, Spain and Slovakia during the COVID-19 Pandemic

Abstract: (1) The COVID-19 pandemic poses threats to human life and health around the world. This study attempts to determine the correlation between loneliness and satisfaction with life among nursing students in Poland, Spain and Slovakia and to seek predictors of social and emotional loneliness among the students. (2) A total of 756 nursing students from Poland, Spain and Slovakia took part in the study. A diagnostic survey was applied as the research method, and the data were collected with the sense of loneliness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
9
0
3
Order By: Relevance
“…Cacioppo et al found that 20–48% of the young adults and adolescents in their study reported loneliness, often high in severity [ 3 ]. These groups may have the highest percentages among all population groups [ 5 , 46 , 47 ]. For nursing students, the restriction or blocking of their interpersonal contact during the COVID-19 pandemic may have played a significant role in developing or increasing feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cacioppo et al found that 20–48% of the young adults and adolescents in their study reported loneliness, often high in severity [ 3 ]. These groups may have the highest percentages among all population groups [ 5 , 46 , 47 ]. For nursing students, the restriction or blocking of their interpersonal contact during the COVID-19 pandemic may have played a significant role in developing or increasing feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…People’s responses during this time have varied because of the “novelty” of the situation, which manifested itself in a reduced scale of contact with other people and difficulty participating in social or professional life [ 1 ]. The extent of the situation justifies the claim that a certain part of the population experiences loneliness [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 93%
“…The results of the current study are consistent with those of previous multi-center studies in which the fatigue severity, in general terms, in the group of Polish students achieved a score of 55.53 points. In addition, the authors demonstrated, for nursing students from three European countries, that the fatigue severity was significantly greater among Polish and Slovakian students than in the Spanish group [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical residents commonly experience poor mental and physical health due to their demanding jobs [8]. Loneliness has a detrimental effect on professional performance, leading to poor treatment outcomes [9]. Both loneliness and social isolation may have been aggravated in medical residents during the COVID-19 pandemic due to quarantine restrictions and avoiding gathering.…”
mentioning
confidence: 99%
“…Both loneliness and social isolation may have been aggravated in medical residents during the COVID-19 pandemic due to quarantine restrictions and avoiding gathering. Speci cally, in the second year of the COVID-19 pandemic, a cross-sectional study of 756 nursing students from Poland, Spain, and Slovakia found that life satisfaction was the main predictor of loneliness [9]. Another cross-sectional survey involving 108 intern doctors in Bangladesh found that insomnia was positively correlated with loneliness [6].…”
mentioning
confidence: 99%